Vehicle choices for teenage drivers: A national survey of U.S. parents. (December 2015) - Eichelberger, Angela H.; Teoh, Eric R.; McCartt, Anne T.
Abstract: Introduction: Previous research has shown that many newly licensed teenagers in the United States are driving vehicles with inferior crash protection. The objective of this study was to update and extend previous research on U.S. parents' choices of vehicles for their teenagers. Method: Telephone surveys were conducted with parents in May 2014 using a random sample of U.S. households likely to include teenagers. Participation was restricted to parents or guardians of teenagers who lived in the household and held either an intermediate or full driver's license. Parents were interviewed about the vehicle their teenager drives, the reason they chose the vehicle for their teenager, and the cost of purchased vehicles. Results: Teenagers most often were driving 2000–06 model year vehicles (41%), with 30% driving a more recent model year and 19% driving an older model year. Teenagers most often were driving midsize or large cars (27%), followed by SUVs (22%), mini or small cars (20%), and pickups (14%). Far fewer were driving minivans (6%) or sports cars (1%). Forty-three percent of the vehicles driven by teenagers were purchased when the teenager started driving or later. A large majority (83%) were used vehicles. The median cost of the vehicles purchased was $5300, and the mean purchase price was $9751. Conclusions: Although parents report that the majority of teenagers are driving midsize or larger vehicles, many of these vehicles likely do not have key safety features, such as electronic stability control, which would be especially beneficial for teenage drivers. Many teenagers were driving older model year vehicles or vehicle types or sizes that are not ideal for novice drivers. Practical applications: Parents, and their teenage drivers, may benefit from consumer information about optimal vehicle choices for teenagers. Highlights: Many U.S. teenagers drive older model year vehicles or vehicle types or sizes that are not ideal for novice drivers. Many of these vehicles likely do not have key safety features, such as electronic stability control. Parents, and their teenage drivers, may benefit from consumer information about optimal vehicle choices for teenagers.